Long‐term treatment with nintedanib in Asian patients with idiopathic pulmonary fibrosis: Results from INPULSIS®‐ON. Issue 4 (22nd July 2019) - Song, Jin Woo; Ogura, Takashi; Inoue, Yoshikazu; Xu, Zuojun; Quaresma, Manuel; Stowasser, Susanne; Stansen, Wibke; Crestani, Bruno
ABSTRACT: Background and objective: The efficacy and safety of nintedanib in patients with idiopathic pulmonary fibrosis (IPF) were investigated in the placebo‐controlled INPULSIS® trials. All patients who completed an INPULSIS® trial could receive open‐label nintedanib in the extension trial INPULSIS®‐ON. Methods: We assessed the long‐term efficacy and safety of nintedanib in patients of Asian race who were treated in INPULSIS®‐ON. Analyses were descriptive. Results: A total of 215 Asian patients were treated in INPULSIS®‐ON, of whom 121 continued nintedanib in INPULSIS®‐ON and 94 initiated nintedanib in INPULSIS®‐ON having received placebo in an INPULSIS® trial. At baseline of INPULSIS®‐ON, the mean (SD) age of Asian patients was 66.3 (7.5) years, 80.5% were males and mean (SD) forced vital capacity (FVC) was 78.9 (19.3) % predicted. Median total exposure to nintedanib in both INPULSIS® and INPULSIS®‐ON was 42.2 months; maximum exposure was 64.1 months. In INPULSIS®, the annual rate (SE) of decline in FVC over 52 weeks in Asian patients was −124 (20) mL/year in the nintedanib group and −218 (24) mL/year in the placebo group. In INPULSIS®‐ON, the annual rate (SE) of decline in FVC over 192 weeks in Asian patients was −127 (11) mL/year. Diarrhoea was reported in Asian patients at event rates of 58.8 and 82.5 events per 100 patient exposure–years in patients who continued and initiated nintedanib in INPULSIS®‐ON, respectively. Conclusion: The effect of nintedanib on slowing disease progression in Asian patients with IPF is sustained over the long term. Long‐term treatment with nintedanib has an acceptable safety and tolerability profile. Abstract : In a subgroup analysis of data from the open‐label extension of the INPULSIS® trials, INPULSIS®‐ON, the effect of nintedanib on slowing disease progression in Asian patients with idiopathic pulmonary fibrosis was sustained over the long term. Long‐term treatment with nintedanib had an acceptable safety and tolerability profile.